Stress and optimism of elderlies who are caregivers for elderlies and live with children - Nathalia Alves de Oliveira; Érica Nestor Souza; Bruna Moretti Luchesi; Keika Inouye; Sofia Cristina Iost Pavarini
ABSTRACT Objective: to evaluate the relation between stress and optimism of elderlies who are informal caregivers for elderlies and live with children. Method: cross-sectional study on 50 elderlies who provide care to elderlies, live with children, and are registered in the primary health care. The interviews occurred in the participant's residence and we evaluated characteristics of the care-dependent elderly and of the children, sociodemographic characteristics, stress through the Perceived Stress Scale and optimism through the Pinto and Pais-Ribeiro Spirituality Scale, in the elderly caregiver. For statistical analysis we used the Spearman correlation test. Results: the mean level of stress was 23.9 points and of optimism was 3.3 points. Correlation analysis showed that the higher the level of optimism the significantly lower the level of perceived stress of elderlies who provided care to elderlies and lived with children. Conclusion: inversely proportional correlation was identified between stress and optimism.